Perilaku Pedagang dalam Membuang Sampah (Studi Kasus di Kawasan Pasar Induk Padang Panjang Kota Padang Panjang). - Muhammad Fauzan; ahyuni .; afdhal . (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This study aims to find out 1) the socio-demographic of traders, 2) the forms of traders 'behavior in disposing of garbage, 3) the availability of landfills and 4) the traders' understanding of market hygiene regulations. The type of research used is descriptive quantitative. This research was conducted in September-November 2018 in Padang Panjang Main Market, Padang Panjang City. The population in this study were all official traders in the Padang Panjang Main Market as many as 800 people and the sampling technique used random sampling as many as 100 people. Data collection techniques in this study were using questionnaires and documentation. The technique of analyzing research data uses percentages. The results of research on the behavior of traders in disposing of garbage in the Padang Panjang Induk Market in Padang Panjang City can be concluded: 1) The sex of the traders who dominate women, the age of traders who dominate 30-39 years, the average length of traders selling 11-20 years, types of merchandise most of which are sold, namely food. 2) The form of behavior carried out by most traders provides cleaning tools, on average they choose to stay quiet in terms of collecting garbage, on average cleaning merchandise before and after selling, most traders throw trash around the kiosk, flat -If the traders dispose of garbage in its place, most traders pay market retribution.3) On average traders have trash bins, most of the trash bins belong to the merchants themselves, on average traders who do not have trash bins have been provided by officers, on average the average trash can is in the form of a plastic barrel, most of the trash cans are covered and waterproof, and those that don't have garbage fulfill the requirements to be replaced. 4) The average trader knows the market hygiene regulations, generally there are regulations made by the manager, most do not know the contents of the hygiene regulations, most comply with the rules and are willing to accept sanctions if they violate, most traders listen to information for maintain cleanliness, generally get counseling about cleanliness and waste management. Keywords: Trader Behavior